Two-step advanced numerical approach for the design of low-cost unbonded fiber reinforced elastomeric seismic isolation systems in new masonry buildings. (August 2018) - Habieb, Ahmad Basshofi; Milani, Gabriele; Tavio, Tavio
Abstract: In developing countries, masonry is generally employed in the construction of residential buildings due to its relatively cheap cost. However, these structures are often provided with inadequate seismic protection. A low-cost base isolation aimed at decreasing the seismic vulnerability of masonry buildings is studied in this work from a numerical standpoint. The studied isolator is an unbonded fiber-reinforced elastomeric isolator (UFREI). With fewer rubber pads than conventional isolators, the UFREI is a cheaper option. A 3D finite element analysis is performed to predict the behavior of the UFREI under large displacements. The isolation system is then implemented into a two-story masonry building prototype, where the 3D model of a single UFREI is substituted by a nonlinear spring and a damper. This simplification decreases the computational costs of the analysis. Seven scaled ground motions are applied to the numerical model to investigate the seismic performance of the isolated masonry building subjected to a maximum considered earthquake. Nonlinear dynamic analyses are performed in Abaqus, taking into account the two horizontal components of the seismic motion. Numerical results show an excellent isolation performance of the system, with a significant reduction of the inter-story drift and a suitable deformation of the UFREIs, as well as demonstrate that the simplified numerical approach adopted is useful for practical design and quick safety assessments. Highlights: Two-step FE procedure for the design of low cost rubber isolation systems in developing countries Unbonded fiber reinforced elastomeric isolator (UFREI) with small dimensions and shape factor Two-phase procedure based on an advanced numerical approach in ABAQUS code Phase 1: 3D-FE non-linear analyses to predict the behavior of the device under large deformations Phase 2: non-linear dynamic analyses on entire buildings isolated with identified spring-dampers.